The opposite of everyone - Jackson, Joshilyn (William Morrow, an imprint of HarperCollinsPublishers, 2016)
After being placed in foster care, Paula Vauss grows up to become a tough divorce attorney only to have her life thrown into chaos by an astonishing revelation and a cryptic message from the mother she has not seen in years.